2012
DOI: 10.1007/s10640-012-9598-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Mortality and Economic Costs of Particulate Air Pollution in Developing Countries: The Case of Nigeria

Abstract: The value of statistical life is an essential parameter used in ascribing monetary values to the mortality costs of air pollution in health risk analyses. However, this willingness to pay estimate is virtually non-existent for most developing countries. In the absence of local estimates, two major benefit transfer approaches lend themselves to the estimation of the value of statistical life: the value transfer method and the meta-regression analysis. Using Nigeria as a sample country, we find that the latter m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 50 publications
(69 reference statements)
1
25
0
5
Order By: Relevance
“…Several studies have also shown that the ambient levels of indoor and outdoor pollutants in many developing urban cities is substantial56789 and associated with huge cost in economic terms and mortality 5. There are various sources of environmental pollution including traffic-related air pollution (TRAP).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also shown that the ambient levels of indoor and outdoor pollutants in many developing urban cities is substantial56789 and associated with huge cost in economic terms and mortality 5. There are various sources of environmental pollution including traffic-related air pollution (TRAP).…”
Section: Introductionmentioning
confidence: 99%
“…Willingness-to-pay studies have shown most people are willing to pay a large proportion of their income in exchange for reduced mortality risks, and data from such studies underlie the VLW methodology. 28,32,49 A handful of previous studies have attempted to estimate the global economic consequences of disease using the WHO EPIC model. 2,7,14 Notably, Alkire et al estimated the global economic consequences of 5 surgical disease categories and projected $12.3 trillion in GDP losses between 2015 and 2030.…”
Section: Discussionmentioning
confidence: 99%
“…Health risk assessment of PM 10 A relative risk model based on Poisson regression, commonly used in epidemiological studies of air pollution to calculate the relative risk of inhalable particulates with certain health impacts, can be used to model PM 10 health risk characterization (Kan and Chen 2004;Yaduma et al 2013). Average relative risk of all health impacts can then be used to represent health risk of inhalable particulate matter using the following equations (Xu et al 2014):…”
Section: Deposition Rate Prediction Modelingmentioning
confidence: 99%